2006
DOI: 10.5301/hip.2009.716
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanics of a new short-stemmed uncemented hip prosthesis: An in-vitro study in human bone

Abstract: The migration pattern, cyclic motion, system stiffness and failure load of a new short-stemmed hip prosthesis were compared to a clinically successful shaft prosthesis during the initial loading phase. The influence of implant-sizing on mechanical stability was also investigated for the new stem, in particular with relation to the bone quality. Prostheses were implanted in paired human femora and loaded cyclically up to 3515 cycles. Relative displacements between prosthesis and bone were measured using a 3D-ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…It has been reported that a proximal-loading device with extended metaphyseal geometry (lateral flare) preserves bone mass and increases periprosthetic bone stock (Leali and Fetto 2004), and that changes in the pattern of proximal loading stimulate the formation of new bone trabeculae, which stream up to the level of the lateral flare (Walker et al 1999). Radiographic studies (Leali et al 2002) and biomechanical tests (Walker et al 1999, Kim et al 2001, Westphal et al 2006b) have confirmed that this kind of proximal geometry provides effective initial and long-term stability, suggesting that stems could be made shorter than designs that do not incorporate the lateral flare feature. Following this philosophy, an original custom-made ultra-short femoral stem with extensive proximal load transfer was developed (type 1).…”
Section: Introductionmentioning
confidence: 94%
“…It has been reported that a proximal-loading device with extended metaphyseal geometry (lateral flare) preserves bone mass and increases periprosthetic bone stock (Leali and Fetto 2004), and that changes in the pattern of proximal loading stimulate the formation of new bone trabeculae, which stream up to the level of the lateral flare (Walker et al 1999). Radiographic studies (Leali et al 2002) and biomechanical tests (Walker et al 1999, Kim et al 2001, Westphal et al 2006b) have confirmed that this kind of proximal geometry provides effective initial and long-term stability, suggesting that stems could be made shorter than designs that do not incorporate the lateral flare feature. Following this philosophy, an original custom-made ultra-short femoral stem with extensive proximal load transfer was developed (type 1).…”
Section: Introductionmentioning
confidence: 94%
“…In contrast, Guo et al [3] showed that Tri-Lock BPS and Corail stems exhibited favorable outcomes in most radiological indices without significant differences at 4-year follow-up, but Tri-Lock BPS outperformed Corail stems in reducing bone loss around the stem while ensuring initial stability of the prosthesis [3]. This may be attributed to the fact that short wedge stems can differentially reduce the effective load on the distal femur to achieve a better fit with the proximal femur, providing a relatively greater load on the proximal bone and thus reducing the stress shielding of the femur [48,49]. Nonetheless, comparison analyses of radiological indices of Tri-Lock BPS vs Corail stems in DAA-THA have not been conducted.…”
Section: Discussionmentioning
confidence: 99%
“…4 Such an approach provides improved outcomes for patients' treatment and rehabilitation. 5,6 Furthermore, AM enables obtaining devices with complex unstructured geometry. Such structures may have not unique mechanical properties but even novel biological features.…”
Section: Introductionmentioning
confidence: 99%
“…Additive manufacturing (AM) brings many benefits to the fabrication of high‐quality porous patient‐specific implants 4 . Such an approach provides improved outcomes for patients' treatment and rehabilitation 5,6 . Furthermore, AM enables obtaining devices with complex unstructured geometry.…”
Section: Introductionmentioning
confidence: 99%